What causes the delay in reforms in Europe? - Malte Rieth; Lisa Gehrt (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The academic literature provides no clear answer to this question. In principle, the recent slowdown in reform activity and fiscal consolidation in the euro area may derive from several developments. Potential reasons involve the end of the economic recession, the provision of financial assistance to crisis countries, and improved financing conditions for governments as a result of unconventional monetary policy, which all reduced reform pressure. While existing studies analyse several of these causes of reform delays in general, there is only very limited evidence for such a relation in the current environment in the euro area.
Keywords: 330; Politische Reform; Haushaltskonsolidierung; Wirkungsanalyse; Eurozone